KONTRIBUSI PENDIDIKAN IPS DALAM MENGHADAPI TANTANGAN DI MASA NEW NORMAL - Imam Bukhari; Nining Winarsih (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
The discovery of the coronavirus (SARS-CoV-2) and the spread of Covid-19 have caused the governmentto take drastic steps, namely taking a lockdown policy for the majority of the population. This research isused to determine or identify people's attitudes in the new normal era. Data analysis in this study wascarried out by researchers from the beginning, in every aspect of research activities. The data analysis stepthat the researchers used was the data analysis of the Miles and Huberman models carried out in this casestudy research were as follows: (1) data reduction; (2) display or presentation of data; (3) verification ordraw conclusions. Currently the Covid-19 outbreak is considered a transnational emergency. Apart fromthe human tragedy of the Covid-19 pandemic, this virus also has an increasingly large impact in variousfields. The education sector also experienced significant disruptions. Education from the community meanseducation provides answers to community needs. Education by the community means that the communityis placed as the subject / actor of education, not the object of education. In this context, society is requiredto play an active role and participation in every educational program.Keywords: Social Studies Education, Covid 19, New Normal Era